2022
DOI: 10.3390/molecules27155000
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Estradiol Benzoate as an Inhibitor of HBx Using Inducible Stably Transfected HepG2 Cells Expressing HiBiT Tagged HBx

Abstract: HBx plays a significant role in the cccDNA epigenetic modification regulating the hepatitis B virus (HBV) life cycle and in hepatocyte proliferation and carcinogenesis. By using the sleeping-beauty transposon system, we constructed a tetracycline-induced HBx-expressing stable cell line, SBHX21. HBx with a HiBiT tag can be quickly detected utilizing a NanoLuc-based HiBiT detection system. By screening a drug library using SBHX21 cells, we identified estradiol benzoate as a novel anti-HBx agent. Estradiol benzoa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Accordingly, Estradiol benzoate has been reported in numerous instances where it has been used as a competitive drug to inhibit viral growth. The antiviral activity of Estradiol benzoate against SARS-CoV-2 and the hepatitis B virus has been previously reported [ 52 , 55 , 56 ]. By binding to and disrupting the six-helix (6-HB) fusion core of SARS-CoV-2 S protein, Estradiol benzoate is able to block viral entry [ 56 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, Estradiol benzoate has been reported in numerous instances where it has been used as a competitive drug to inhibit viral growth. The antiviral activity of Estradiol benzoate against SARS-CoV-2 and the hepatitis B virus has been previously reported [ 52 , 55 , 56 ]. By binding to and disrupting the six-helix (6-HB) fusion core of SARS-CoV-2 S protein, Estradiol benzoate is able to block viral entry [ 56 ].…”
Section: Resultsmentioning
confidence: 99%
“…By binding to and disrupting the six-helix (6-HB) fusion core of SARS-CoV-2 S protein, Estradiol benzoate is able to block viral entry [ 56 ]. Using HepG2.2.15 cells and HepG2 transfected cells as a cellular model of HBV replication, it was also found that Estradiol benzoate inhibited HBV replication and transcription [ 55 ].…”
Section: Resultsmentioning
confidence: 99%